1996
DOI: 10.1016/s0006-3495(96)79370-0
|View full text |Cite
|
Sign up to set email alerts
|

The pore domain of the nicotinic acetylcholine receptor: molecular modeling, pore dimensions, and electrostatics

Abstract: The pore domain of the nicotinic acetylcholine receptor has been modeled as a bundle of five kinked M2 helices. Models were generated via molecular dynamics simulations incorporating restraints derived from 9-A resolution cryoelectron microscopy data (Unwin, 1993; 1995), and from mutagenesis data that identify channel-lining side chains. Thus, these models conform to current experimental data but will require revision as higher resolution data become available. Models of the open and closed states of a homopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 75 publications
3
58
0
Order By: Relevance
“…The conception of hydrophilic residues lining the pore is based on experimental findings in the pore-lining helices of the nicotinic acetylcholine receptor (nAChR) (38)(39)(40)(41). Computational studies have used these findings to generate not only equivalent bundles of M2 from nAChR (31,32) but also bundles of the TM domain of the influenza A channel protein M2 (33) and the channel protein NB from influenza B (34). However, recent studies also show that the positioning of tryptophans toward the center of the pore can result in a model representing a stable "closed" structure (21,24,42).…”
Section: Discussionmentioning
confidence: 99%
“…The conception of hydrophilic residues lining the pore is based on experimental findings in the pore-lining helices of the nicotinic acetylcholine receptor (nAChR) (38)(39)(40)(41). Computational studies have used these findings to generate not only equivalent bundles of M2 from nAChR (31,32) but also bundles of the TM domain of the influenza A channel protein M2 (33) and the channel protein NB from influenza B (34). However, recent studies also show that the positioning of tryptophans toward the center of the pore can result in a model representing a stable "closed" structure (21,24,42).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several proposed molecular models of the transmembrane domain of the a7 nAChR 37,38 and cryo-electron microscopy images have been used to develop models of the Torpedo marmorata nAChR (abdg nAChR). 39 We have recently reported a model of the central lumen of the a3b4 nAChR, which can be used to describe the binding and function of NCIs to this receptor.…”
Section: Molecular Models Of the Luminal-binding Sitementioning
confidence: 99%
“…Molecular modelling studies restrained by cryoelectron microscopy data indicate that the M2 helices are kinked. 7,8 The kink is thought to be in the vicinity of a Leu residue that is conserved between subunits and between nicotinic receptors from different species. This Leu has been suggested to play a role in the gating mechanism of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…This Leu has been suggested to play a role in the gating mechanism of the channel. It is suggested that the helix kink may correspond to a molecular hinge, 3,8 enabling changes in conformation and packing of the M2 helices in response to binding of neurotransmitter and resulting in a switch from a closed (i.e., ion impermeable) to an open (i.e., ion permeable) channel.…”
Section: Introductionmentioning
confidence: 99%